The Influence of Social Media on the Attitude of Religious Moderation among College Students - Baedowi, Muhamad; Chamadi, Muhammad Riza; Musmuallim; Turhamun (Yayasan Sinergi Kawula Muda, 2025)
In the digital age, social media has become a powerful instrument in shaping public opinion, including religious perspectives among college students. The proliferation of religious content across platforms such as Instagram, TikTok, YouTube, and Facebook presents both opportunities and challenges for fostering religious moderation. This study aims to examine how social media influences students’ attitudes toward religious moderation, with a particular focus on core values such as justice ('adl), balance (tawazun), and tolerance (tasamuh). The research adopts a qualitative literature review method, analyzing scholarly articles, books, and official publications published within the last five years that discuss the relationship between social media, youth behavior, and religious moderation. The findings indicate that social media plays a dual role. On one hand, it serves as a platform for promoting inclusive and moderate religious messages, often through visually engaging and relatable content. On the other hand, the same platforms may also disseminate radical ideologies, hate speech, and intolerant narratives, particularly when users lack digital literacy and critical thinking skills. The study highlights the importance of equipping students with the ability to critically evaluate religious content on social media and to distinguish between authentic moderation messages and manipulative, extremist discourse. In conclusion, this study underscores the necessity of integrating religious moderation into digital literacy education within higher education institutions. Collaborative efforts between educators, religious leaders, and content creators are essential in ensuring that digital spaces are dominated by constructive and peaceful religious narratives. The role of students as digital natives and future agents of change makes their involvement in this discourse both timely and essential.